2022
DOI: 10.1139/as-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring litter and microplastics in Arctic mammals and birds

Abstract: Plastic pollution has been reported to affect Arctic mammals and birds. There are strengths and limitations to monitoring litter and microplastics using Arctic mammals and birds. One strength is the direct use of these data to understand the potential impacts on Arctic biodiversity as well as effects on human health, if selected species are consumed. Monitoring programs must be practically designed with all purposes in mind, and a spectrum of approaches and species will be required. Spatial and temporal trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 145 publications
(224 reference statements)
0
7
0
Order By: Relevance
“…In a particularly incredible example, Fjelldal et al (2021) found wild Atlantic salmon and sea-run brown trout smolts had entered experimental fish farms during their seaward migration and become trapped, growing up in the farm until it was emptied. Similarly, Losey, Rayor & Carter (1999) showed that genetically modified maize plants expressing crystalloproteins from the soil bacterium Bacillus thuringiensis increased mortality of monarch butterfly larvae by 44%.…”
Section: Iucn Threat Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…In a particularly incredible example, Fjelldal et al (2021) found wild Atlantic salmon and sea-run brown trout smolts had entered experimental fish farms during their seaward migration and become trapped, growing up in the farm until it was emptied. Similarly, Losey, Rayor & Carter (1999) showed that genetically modified maize plants expressing crystalloproteins from the soil bacterium Bacillus thuringiensis increased mortality of monarch butterfly larvae by 44%.…”
Section: Iucn Threat Taxonomymentioning
confidence: 99%
“…Garbage dumps can serve as ecological traps for migratory vultures (Buechley et al ., 2018) and alter natural feeding regimes for a variety of birds (Tortosa, Caballero & Reyes‐López, 2002). Plastic debris such as lost fishing gear has been observed to entangle migratory wildlife such as humpback whales ( Megaptera novaeangliae ; Gregory, 2009) and the Critically Endangered North Atlantic right whale ( Eubalaena glacialis ; Knowlton et al ., 2022), while plastics (micro and macro) may be ingested by a variety of taxa creating bezoars that impact nutrition and eventually can result in inability to migrate (or death; Lusher et al ., 2022). Compared to the obvious negative effects of macroplastics (de Stephanis et al ., 2013; Cartarud et al ., 2019), the consequences of microplastics on migratory birds are unclear despite evidence that they are common (Hoang & Mitten, 2022).…”
Section: Iucn Threat Taxonomymentioning
confidence: 99%
“…The transport of plastic additives with migratory species can take place via ingestion of plastic particles on migratory routes. The ingestion of plastics (and consequently, plastic chemical additives) has been studied in the Arctic in a variety of wildlife species, including whales and a number of seabird species which can migrate over long distances (Lusher et al 2022). Independent of migratory behaviour, numerous free-ranging Arctic vertebrates are likely regularly exposed to plastic additives upon ingestion of plastic particles.…”
Section: Plastic Materials As Chemical Vectorsmentioning
confidence: 99%
“…Microplastics have been reported in freshwater [ 5 , 6 ], groundwater [ 7 , 8 ], soil [ 9 , 10 ], sediment [ 11 , 12 ], snow [ 13 , 14 ], ice [ 15 , 16 ], and air [ 17 , 18 ]. Many studies have shown that microplastics are ingested by various organisms [ 19 , 20 , 21 ], invertebrates [ 22 , 23 ], mammals [ 24 , 25 ], and birds [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%